2023
DOI: 10.1021/acs.macromol.3c02222
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Catalysts: Regulating Multimetal Cooperativity for CO2/Epoxide Copolymerization

Liehang Yang,
Shunjie Liu,
Zhenzhen Zhou
et al.

Abstract: Biomimetic aggregates have flourished in various fields, particularly in small-molecule catalysis, but their application in polymer synthesis remains understudied. Herein, we propose a strategy for constructing aggregate catalysts based on aggregationregulating cooperativity to enhance the copolymerization of CO 2 / propylene oxide (PO). The key design strategy involves constructing polymeric aluminum porphyrin catalysts (PAPCs) with varied stacking modes induced by substituents' electronic effects, enabling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 64 publications
(103 reference statements)
0
0
0
Order By: Relevance
“…An elevation in the reaction temperature from 70 to 100 °C, 120 °C, and then to 140 °C led to a notable enhancement in the catalytic activity from 5000 to 20000 h –1 , 19000 h –1 , and then to 25200 h –1 , respectively (Table , entries 2, 5–7). Furthermore, polymer selectivity was maintained at a high level (>90%), outperforming the previously reported polymeric aluminum catalyst (polymer selectivity% = 81%, TOF = 12600 h –1 , 130 °C) . Owing to the use of rigid skeleton and the π–π interactions between porphyrin units, the catalyst demonstrates resilience to elevated temperatures of up to 160 °C without significant activity drop (Figure c), but it displays limited selectivity toward polymers (76%).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…An elevation in the reaction temperature from 70 to 100 °C, 120 °C, and then to 140 °C led to a notable enhancement in the catalytic activity from 5000 to 20000 h –1 , 19000 h –1 , and then to 25200 h –1 , respectively (Table , entries 2, 5–7). Furthermore, polymer selectivity was maintained at a high level (>90%), outperforming the previously reported polymeric aluminum catalyst (polymer selectivity% = 81%, TOF = 12600 h –1 , 130 °C) . Owing to the use of rigid skeleton and the π–π interactions between porphyrin units, the catalyst demonstrates resilience to elevated temperatures of up to 160 °C without significant activity drop (Figure c), but it displays limited selectivity toward polymers (76%).…”
Section: Resultsmentioning
confidence: 65%
“…As depicted in Figure b, the Soret band (400–440 nm) of RFBCs exhibits a significantly broader profile with a shoulder peak, in contrast to m-Al. This observation implies that the two porphyrin units are spatially conjugated and adopt a face-to-face configuration. ,, Significantly, when the distance between the porphyrin units is reduced, the Soret band absorption of RFBCs widens, suggesting an increasing synergy. Both UV–vis and 1 H NMR spectra demonstrated an enhancement in the intramolecular synergy of RFBCs as the proximity between the two porphyrins increased (Figure c).…”
Section: Resultsmentioning
confidence: 95%
“…Previous research has indicated that electron-withdrawing/donating substituents on porphyrins influence π–π interactions and induce distinct stacking modes, such as H-aggregation (face-to-face arrangement) or J-aggregation (edge-to-edge arrangement). 35–37 In this study, using porphyrin monomers carrying –Cl and –Me substituents, we synthesized H-aggregate catalysts (PAPC-Cl) with strong interaction and J-aggregate catalysts (PAPC-Me) with weak interaction, respectively (Scheme S1 and Fig. S1–S13†).…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies have shown that interactions between the porphyrins in individual polymer chains are more efficient at ultra-dilute catalyst concentrations and high temperatures. 35 This insight is crucial for understanding synergistic effects in copolymerization reactions. In conclusion, the construction of these two aggregate catalysts (H- and J-aggregate) set the stage for investigating synergistic effects in polymerization reactions of cyclic anhydrides and epoxides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation